2023
DOI: 10.3390/ejihpe13040052
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Challenge-Based Learning Experience in Physical Education on Students’ Motivation and Engagement

Abstract: The present study investigated how challenge-based learning (CBL) in physical education (PE) may affect students’ basic psychological needs (BPNs), motivational regulations, engagement, and learning in comparison with a traditional teaching (TT) methodology. A quasiexperimental study with experimental and control groups was carried out. In total, 50 participants (16 boys and 34 girls) between 13 and 15 years old (Mage = 13.35, SD = 0.62) were involved in the experience for 6 weeks (ncontrol = 24; nexperimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Although limited, there have been some empirical studies on the impact of CBL on wellbeing-related variables: (1) Regarding engagement, Johnson and Adams (2011) suggest that CBL effectively promotes students’ engagement in learning. Similarly, Simón-Chico et al (2023) found that behavioral engagement ( Fredricks et al, 2004 ; Skinner et al, 2008 ) in the CBL condition in physical education was higher after the intervention than before. (2) A study by Johnson and Adams (2011) suggests that CBL programs effectively enhance students’ social skills.…”
Section: Cbl Should Be Considered As a Part Of Pe And Be Integrated W...mentioning
confidence: 87%
See 3 more Smart Citations
“…Although limited, there have been some empirical studies on the impact of CBL on wellbeing-related variables: (1) Regarding engagement, Johnson and Adams (2011) suggest that CBL effectively promotes students’ engagement in learning. Similarly, Simón-Chico et al (2023) found that behavioral engagement ( Fredricks et al, 2004 ; Skinner et al, 2008 ) in the CBL condition in physical education was higher after the intervention than before. (2) A study by Johnson and Adams (2011) suggests that CBL programs effectively enhance students’ social skills.…”
Section: Cbl Should Be Considered As a Part Of Pe And Be Integrated W...mentioning
confidence: 87%
“… López-Fernández et al (2020) reported improvements in the relationship between teachers and students after they worked collaboratively to solve the challenges in their CBL program. (3) Regarding basic psychological needs ( Chen et al, 2015 ), Simón-Chico et al (2023) reported improvements in autonomy, competence, and relatedness satisfaction after a CBL program.…”
Section: Cbl Should Be Considered As a Part Of Pe And Be Integrated W...mentioning
confidence: 99%
See 2 more Smart Citations
“…During adolescence there is a decrease in the time of physical activities, especially in girls [51]. The interests toward which the subject of physical education is oriented can have a positive or negative impact on the motivations of students [52,53].…”
Section: Discussionmentioning
confidence: 99%